Health related quality of life and social support for women with breast cancer: a literature review - Eugenia Minasidou; Kyriaki Spanoudi; Theodora Kafkia (Ene, 2016)
For many patients, the fulfillment of spiritual and religious needs is more important than the fulfillment of biological and physical needs. Spirituality is defined as the way that the individual gives meaning and purpose to life, as the experience of contact with himself, others, nature and supernatural powers. On the other hand, Religiosity is considered to be the adoption of specific rituals and beliefs within a specific religious framework either publically or privately. It is possible, religiosity to be a means of expression of spirituality. The aim of the present literature review is to describe the concepts of spirituality and religiosity through the international literature, and to look into the possible impact on the quality of life of chronic patients or patients with life-threatening diseases. Spirituality and religiosity seems to have positive effects in disease management and quality of life improvement of thesepatients. The fulfillment of spiritual and religious needs of people with chronic and life-threatening diseases is a priority of the holistic healthcare approach and should be taken under consideration during care planning and implementation of interventions.